Percepção e diagnóstico da Leishmaniose visceral canina em áreas ribeirinhas na cidade de Mossoró, Rio Grande do Norte - Costa, Kalídia Felipe de Lima (Universidade Federal Rural do Semi-Árido, 2014)
Visceral Leishmaniasis (VL) is a zoonosis in which dogs are reservoir in the urban environment and its diagnosis consists in one of the main strategies to control the disease in Brazil. Nevertheless, another important approach for the control and prevention of VL is through the awareness of the population about the disease, which could be promoted with health education practices by health professionals like Agentes Comunitários de Saúde (ACS) (Health Agents for the Community). Thus, the research study aim is to evaluate the population in the riverside areas that are susceptible to VL, likewise the residents that own dogs in their homes and the ACS that work in these areas. The study also aims to evaluate if the Agents includes measures to prevent the disease in their work duty and if the administration of the city of Mossoró, Rio Grande do Norte enables them with vocational training activities and if they facilitate these professionals with good work condition. For that, a research study was made with 79 riverside residents and 42 ACS. For both riverside residents and ACS, a semi-structured interview about the disease and prevention of VL were performed, the ACS were also questioned about surveillance and control activities developed and about professional training. Additionally, 88 dogs residing in households were included in the survey and were tested for canine VL (CVL) by Polymerase Chain Reaction. The data was analyzed by Qui-quadrado e Exato de Fisher tests (p <0.05). 59% of the riverine population which were interviewed knew how the disease was transmitted, but were unaware that sand-fly was a vector of VL and 58% were unaware of the preventive measures of VL. Regarding human VL, was concluded that they were unaware about the symptoms and treatment; and, there were doubts about whether a vaccine and a cure for the disease existed. About the canine VL was noticed a greater knowledge about the symptoms, cure and euthanasia, but they were unaware about whether a vaccine existed or not. From among the dogs, 32% were positive for Leishmania. When the canine diagnostic test was correlated with the answers of the local population, there was an association with the educational level of the population and the awareness of VL (p<0,05). Regarding the ACS, most of them knew some kind of symptoms of the disease, the cure, and the type of diagnosis, but they were unaware about the treatment and whether a vaccine for VL existed; they also received training about the matter. There was an association of the ACS profile and their participation in vocational training activities, with their knowledge about epidemiological surveillance and the implementation of prevention activities (p <0.05). We have come to the conclusion that both the local population interviewed, as well as the ACS have insufficient knowledge about the VL, constituting in a reflection of the lack of investment in vocational training activities, by the government, undermining the development of health education activities. Furthermore, with the identification of reagents dogs for VL in riverside areas we confirmed the existence of the disease cycle in these areas, leaving both the human population as well as the canine susceptible to the VL
Perception and diagnosis for canine visceral leishmaniasis in riverside areas in the city of Mossoró, Rio Grande do Norte
Keywords: Visceral Leishmaniasis; Population in the Riverside Areas; Public Health; Molecular Diagnosis; Health Agents for the Community; Leishmaniose visceral; população ribeirinha; saúde pública; diagnóstico molecular; agentes comunitários de saúde; MULTIDISCIPLINAR::CIENCIAS AMBIENTAIS::AMBIENTE, TECNOLOGIA E SOCIEDADE